Pengaruh Penambahan Na2CO3 Terhadap Konsistensi Dan Kuat Geser Pada Tanah Lempung - Renaldi, Renaldi Z; Sariman, Syahrul; Setiawan, Arman (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Clay soils in general can be said to have a low carrying capacity. Therefore, it needs to be treated if it will be used as a construction base. This study aims to determine the effect of adding Na2CO3 (sodium carbonate) on the consistency and shear strength in clay soils. This study was conducted by preparing a mixture of various concentrations of Na2CO3, namely 0.4%, 0.6%, 0.8% and 1.0%, which were added to clay soil samples, which is added to clay soil samples. Consistency testing using the Atterberg limit test (Casagrande Stone). The results showed that the addition of Na2CO3 had an influence on the consistency of clay soil. In the shear strength test, there are values of cohesion, shear angle and shear strength, where the percentage of mixture increases. So that in this test the optimum shear strength value can be obtained on a mixture of 1% Na2CO3 soil.